Accuracy of reticulocyte hemoglobin for diagnosing iron deficiency in former very preterm infants: a population-based cohort study - Barr, Hudson; Kulkarni, Ketan; Singh, Balpreet; Sandila, Navjot; Morrison, Lisa; Beach, Lori; Ghotra, Satvinder (Frontiers in Pediatrics, 2023)
Background: Serum ferritin (SF) is commonly used to diagnose iron deficiency (ID) but has limitations. Reticulocyte hemoglobin (Ret-He) is being increasingly used for ID diagnosis. This study aimed to assess accuracy of Ret-He for ID diagnosis in former very preterm infants (VPI) at 4-6 months corrected age (CA). Methods: A retrospective population-based cohort study was conducted on all live VPI born between 23 and 30 weeks of gestational age (GA) in Nova Scotia from 2012 to 2018. Infants underwent SF and Ret-He testing at 4-6 months CA. ID was defined using two definitions. The first defined ID as SF <20mcg/L at both 4-and 6-months CA, and the second as SF <20mcg 30mcg at at both 4-and 6months CA4 months and <12mcg/L at 6 months CA. The accuracy of Ret-He for identifying ID was assessed using the area under the receiver operating characteristic curve (AUC). Results: ID was present in 39.7% (62) of 156 infants in the first definition and 59.625.0% (3993) in the second at 4-6 months CA. The AUC of Ret-He for ID diagnosis was 0.64 (p=0.002) in the first definition and 0.69 0.59 (p<0.001=0.041) in the second. The optimal cut-off was 29.4pg in the first and 29.7 in the second regardless of definition. The sensitivity, specificity, positive predictive value (PPV), and negative predictive values (NPV) at the 29.4pg this cut-off were 50.0%, 78.7%, 60.8%, and 70.5% for definition 1 and 44.1%59.0%, 76.1%74.6%, 45.171.9%%, and 84.8%47.5% at the 29.7pg cut-off for definition 2. Conclusion: Ret-He had low diagnostic accuracy for ID diagnosis in former VPI. Caution is advised when using Ret-He alone for ID diagnosis. Further research is needed to establish optimal approaches for identifying ID in VPI.